Catechol‐O‐methyltransferase, a new target for pancreatic cancer therapy. Issue 5 (25th March 2015) - Wu, Wenming; Wu, Qiao; Hong, Xiafei; Zhou, Li; Zhang, Jie; You, Lei; Wang, Wenze; Wu, Huanwen; Dai, Hongmei; Zhao, Yupei
<x xml:space="preserve">Abstract</x> Catechol‐O‐methyltransferase (COMT) is an important molecule in different types of cancers. Its biological effect and therapeutic significance, however, rarely been investigated fully in pancreatic cancer. Immunohistologically, high COMT expression was significantly correlated with the longer overall survival of patients (P < 0.05), indicating its protective nature. The effects of COMT on cell growth, apoptosis, and invasion were evaluated using overexpression and silencing methods. In detail, we carried out experiments using one stably transduced and two transiently transfected pancreatic cancer cell lines in vitro, and one stably transduced cell line in vivo mice xenograft models. In vitro experiments showed that COMT inhibited cell proliferation, enhanced gemcitabine‐induced apoptosis, and inhibited cell invasion in stably transduced and transiently transfected cell lines by regulating the PI3K/Akt pathway, p53, and E‐cadherin. The COMT overexpressed and silenced cell lines showed significantly inhibited and enhanced growth capacities in in vivo xenograft models, respectively. In conclusion, COMT suppressed pancreatic cancer and its high expression predicted longer survival time. The interaction of COMT with the PI3K/Akt pathway makes it a potential target for therapy.